Multifaced Endophytic Pseudomon As Fluorescens For Inducing Growth Promoting Activity In Cotton (Journal of Plant Disease Sciences, 2020)
The cotton need treated with microbial bio-formulation containing endophytic Pseudomonas fluorescens, were assessed for the growth promotion by roll towel method. Higher seedling vigour index (1918.00) was recorded in Pf-1 treated seeds compared to control (50.88).The strains Pf were characterized by performing various biochemical studies and these strains produced higher amount of viz., IAA, siderophore, HCN, ACCD production and growth promotion of ACCD treated cotton seeds were assessed and growth promotion was recorded compared to control.
Keywords: Cotton; Endophytes; Pseudomonas fluorescens; Growth promotion